Keeping football in the family - Maddox, Jake; Mauleón, Daniel, 1991- (Jake Maddox graphic novels., 2023)
Alejandro is having trouble living up to his brother's reputation as a great high school quarterback, and the coach is threatening to bench him. Could his sister Izzy be the secret weapon he needs?